Relationship index kinetic energy corner of the trunk and the high center of gravity of the body in three-point correction of the basketball jump - Faris, Laith (Journal of Physical Education, 2007)
The Research aims at identifying the relationshop between the indicator of angular kinetic energy and three points jump shot as well as the relationshop between the center of body weight at the highest point and jump shot scoring. It also aims at identifying the relationshop between mechanical variables (angular kinetic energy indicator and the height of body weight at the highest point) and their effect on accuracy of scoring in Basketball. The subjects were (10) elite basketball players from (Al-Kerk, Al-Gaish, Al-Adamia, Al-Hilla, Dehook clubs), The researcher desigened a from to test the players who could perform the three point jump shot and the best were chosen for the test. After that the researcher designed a special form to test three point jump shot and he video taped the players during performance. The researcher used proper statistical methods and came up with a set of conclusions